Low-temperature culture enhances production of flavivirus virus-like particles in mammalian cells - Fan, Yi-Chin; Chen, Jo-Mei; Chen, Yi-Ying; Hsu, Wei-Li; Chang, Gwong-Jen; Chiou, Shyan-Song (Applied microbiology and biotechnology, 2024)
Flavivirus virus-like particles (VLPs) exhibit a striking structural resemblance to viral particles, making them highly adaptable for various applications, including vaccines and diagnostics. Consequently, increasing VLPs production is important and can be achieved by optimizing expression plasmids and cell culture conditions. While attempting to express genotype III (GIII) Japanese encephalitis virus (JEV) VLPs containing the G104H mutation in the envelope (E) protein, we failed to generate VLPs in COS-1 cells. However, VLPs production was restored by cultivating plasmid-transfected cells at a lower temperature, specifically 28 °C. Furthermore, we observed that the enhancement in JEV VLPs production was independent of amino acid mutations in the E protein. The optimal condition for JEV VLPs production in plasmid-transfected COS-1 cells consisted of an initial culture at 37 °C for 6 h, followed by a shift to 28 °C (37/28 °C) for cultivation. Under 37/28 °C cultivation conditions, flavivirus VLPs production significantly increased in various mammalian cell lines regardless of whether its expression was transiently transfected or clonally selected cells. Remarkably, clonally selected cell lines expressing flavivirus VLPs consistently achieved yields exceeding 1 μg/ml. Binding affinity analyses using monoclonal antibodies revealed similar binding patterns for VLPs of genotype I (GI) JEV, GIII JEV, West Nile virus (WNV), and dengue virus serotype 2 (DENV-2) produced under both 37 °C or 37/28 °C cultivation conditions. In summary, our study demonstrated that the production of flavivirus VLPs can be significantly improved under 37/28 °C cultivation conditions without affecting the conformational structure of the E protein. Keypoints • Low-temperature culture (37/28 °C) enhances production of flavivirus VLPs. • Flavivirus VLPs consistently achieved yields exceeding 1 μg/ml. • 37/28 °C cultivation did not alter the structure of flavivirus VLPs.